2019
DOI: 10.1016/j.hrthm.2019.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Algorithm-based reduction of inappropriate defibrillator shock: Results of the Inappropriate Shock Reduction wIth PARAD+ Rhythm DiScrimination–Implantable Cardioverter Defibrillator Study

Abstract: BACKGROUND Inappropriate shocks (IS) continue to have a major negative impact on patients implanted with defibrillators.OBJECTIVE The purpose of this study was to assess IS reduction with the PARAD1 discrimination algorithm in a general population implanted for primary or secondary prevention. METHODS ISIS-ICD (Inappropriate Shock Reduction wIth PARAD1Rhythm DiScrimination-Implantable Cardioverter Defibrillator) was a 2-year international, interventional study in patients implanted with a dual implantable card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…Appropriate ICD therapy was delivered in 13.4% of the study cohort, whereas appropriate shocks were mandated in 5.0% of patients at 2 years. Consistently with previous studies, 5 a lower rate of appropriate shocks is found in the CRT-D arm. The rate of appropriate ICD shocks in CARAT was lower than in recently published trials such as the EU-CERT trial (7.1% within 2.7 years) 9 and the PRAETORIAN trial (19.5% in the subcutaneous ICD subgroup and 13.5% in the transvenous ICD subgroup, median follow-up 49.1 months) 6 , 7 and comparable to the DANISH trial (11.5% within 5.5 years), 13 potentially associated with a reduced proportion of ischaemic heart failure aetiology in the present study (51%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Appropriate ICD therapy was delivered in 13.4% of the study cohort, whereas appropriate shocks were mandated in 5.0% of patients at 2 years. Consistently with previous studies, 5 a lower rate of appropriate shocks is found in the CRT-D arm. The rate of appropriate ICD shocks in CARAT was lower than in recently published trials such as the EU-CERT trial (7.1% within 2.7 years) 9 and the PRAETORIAN trial (19.5% in the subcutaneous ICD subgroup and 13.5% in the transvenous ICD subgroup, median follow-up 49.1 months) 6 , 7 and comparable to the DANISH trial (11.5% within 5.5 years), 13 potentially associated with a reduced proportion of ischaemic heart failure aetiology in the present study (51%).…”
Section: Discussionsupporting
confidence: 92%
“…As the PARAD+® algorithm had been used as default tachyarrhythmia detection algorithm in the presence of a functional atrial lead, CARAT confirms results of previous studies such as OPTION 3 , 4 or ISIS-ICD 5 in terms of arrhythmia discrimination in dual-chamber devices. The present study also reports low inappropriate shocks in single-chamber devices, where arrhythmia discrimination is based on a combination of stability, acceleration, and ‘long cycle gap’ to identify atrial fibrillation.…”
Section: Discussionsupporting
confidence: 77%
“…Inappropriate shocks are one of the main issues to be avoided as they cause patient discomfort, are potentially proarrhythmic, and reduce battery life. The two main causes of inappropriate shock are failure in discriminating supraventricular arrhythmias (SVA) [2][3][4][5][6][7][8][9][10][11][12][13]. Frequently SVA is associated with a fast-ventricular response leading ventricular rate to fall into VT/VF detection zone causing inappropriate therapy release.…”
Section: Inappropriate Therapies Due To Supraventricular Tachycardiamentioning
confidence: 99%
“…Signal misinterpretation is the other big deal leading to inappropriate shocks. It may depend on some programmed variables; easily editable, external, and farfield interferences; or lead failure that usually requires an interventional approach [2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Inappropriate Shock Due To Oversensingmentioning
confidence: 99%